Clinical Outcome of Septic Patients With Heart Failure With Preserved Ejection Fraction Presenting to the Emergency Department of a Tertiary Hospital: A Retrospective Cohort Study - Chebl, Ralphe Bou; Berbari, Iskandar; Safa, Rawan; Shami, Ali; Sabra, Mohammad; Jamali, Sarah; Makki, Maha; Tamim, Hani; Dagher, Gilbert Abou (Frontiers in Medicine, 2020)
Background: Patients with heart failure with preserved ejection fraction (HFpEF) may be at a higher risk of mortality from sepsis than patients without HFpEF. Objective: The aim of this study is to compare sepsis-related morbidity and mortality between patients with HFpEF and patients without heart failure presenting to the emergency department (ED) of a tertiary medical center. Design: Single-center retrospective cohort study conducted at an academic ED between January 1, 2014 and December 31, 2018. Patients: Patients with a diagnosis of sepsis were included. Main Measures: Bivariate and multivariate analyses were performed on the demographics, characteristics and outcomes of patients with sepsis. The primary outcome of the study was in-hospital mortality. Secondary outcomes included ED mortality, lengths of stays and differences in interventions between the two groups. Key Results: A total of 1381 patients presented with sepsis to the ED, of which 305 (22.08%) had HFpEF. There was no significant difference in in-hospital mortality between the two groups (40.7% vs 37.4%; p-value=0.314). However, there was a significant increase in ED mortality for septic HFpEF patients compared to controls (2.4% vs 0.4%; p-value=0.003). Septic HFpEF patients presenting to the ED were older than control patients (76.84 vs 68.44 years old; p-value<0.0001). On the other hand, there was no significant increase in the use of norepinephrine, dopamine, epinephrine or dobutamine in the first 24h between the two groups. There was a significantly higher rate of intubation in the first 48h for septic patients with HFpEF (17.5% vs 8.9%; p-value<0.0001). Finally, there was significantly less intravenous fluid requirement at 6h (1.94L vs 2.41L;p-value<0.0001) and 24h (3.11L vs 3.54L; p-value = 0.004) for septic patients with HFpEF compared to controls. Conclusion: Septic HFpEF patients experienced an increase in ED mortality, intubation and steroid use compared to septic patients without HFpEF.